Determination of LD50 of Ethidium Bromide for Induction of Mutation in Marigolds - Keadtidumrongkul, Pornthep; Chirarat, Nawannaporn; Somran, Sophana (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 4 (2018): October-December 2018, 2018)
Mutation is an effective way to increase genetic variability in plant, which can be done in two ways: physical mutation and chemically induced mutation using a chemical mutagen. Ethidium bromide (EtBr) is the most efficient chemical mutagen,  inducing mutation in the mitochondria, chloroplasts and nucleus DNA. To increase genetic variance in marigolds, the appropriate concentration level and soaking periods of EtBr must be identified, which was the purpose of this study. Marigold seeds were soaked with 0, 250, 500, 750 and 1000 mg/l of EtBr for 24, 48 and 72 hours. The results showed that the most appropriate concentration of EtBr for inducing mutation in marigolds (LD 50 ) was 623.81 mg/l for 48 hours. However, increasing the concentration level of EtBr decreased the growth of the marigolds, as measured by the height of the tree, and, further, EtBr markedly reduced the survival percentage, especially at high concentration levels. Keywords: mutagen, genetic variance, lethal dose